The effect of 2-day heat stress on the lipid composition of bovine milk and serum - Li, Cheng; Liu, Zhiqian; Bath, Carolyn; Marett, Leah C.; Pryce, Jennie; Rochfort, Simone (Frontiers in Animal Science, 2023)
Milk and serum were collected from dairy cows before and during a 2-day heat challenge. The concentrations of free short-chain fatty acids (SCFAs), the fatty acid (FA) profile, and the abundance of the major species of phosphatidylcholine (PC), phosphatidylethanolamine (PE), and sphingomyelin (SM) were measured, and samples collected during heat exposure were compared with those collected prior to heat exposure. It was found that a 2-day heat challenge did not alter the global FA composition of milk fat nor the content of the major phospholipids. Although the concentration of SCFAs C3 and C4 and some lysophosphatidylcholine (LPC) species in milk was found to be associated with the forage type, neither of these lipid molecules can be used as an indicator of acute heat stress. While it is a positive finding that short-term heat stress has no detrimental effect on the FA composition or the nutritive quality of milk fat, this study highlights the complexity of validating a milk lipid biomarker for heat stress in dairy cows.